Investigation of converse magnetoelectric thin-film sensors for magnetocardiography - Elzenheimer, Eric; Hayes, Patrick; Thormählen, Lars; Engelhardt, Erik; Zaman, Adrian; Quandt, Eckhard; Frey, Norbert; Höft, Michael; Schmidt, Gerhard (IEEE sensors journal, 2023)
In principle, electrode-based bioelectrical signal acquisition can be complemented by biomagnetic sensing and therefore requires a more detailed assessment, especially because of the availability of novel noncryogenic sensor technologies. The current development of thin-film magnetoelectric (ME) sensors ensures that ME technology is becoming a prospective candidate for biomagnetometry. The main obstacle for large-scale usage is the lack of extremely low noise floors at the final sensor system output. This article highlights the current state of ME sensor development based on a magnetocardiography (MCG) pilot study involving a healthy volunteer in a magnetically shielded chamber. For assessment, an ME prototype (converse ME thin-film sensors) will be applied for the first time. This sensor type ensures a noise amplitude spectral density below 20 pT / \sqrt \text Hz at 10 Hz by using a sophisticated magnetic layer system. The main aim of this pilot study is to evaluate the applicability of this promising sensor for the detection of a human heart signal and to evaluate the sensor output with competitive optical magnetometry technology. A magnetic equivalent of a human R wave could be successfully detected within a 1-min measurement period with the sensor presented here. Finally, the article will provide an outlook on future ME perspectives and challenges, especially for cardiovascular applications.